Carbon monoxide differentially inhibits TLR signaling pathways by regulating ROS-induced trafficking of TLRs to lipid rafts - Nakahira, Kiichi (The Rockefeller University Press, 2006)
Carbon monoxide (CO), a byproduct of heme catabolism by heme oxygenase (HO), confers potent antiinflammatory effects. Here we demonstrate that CO derived from HO-1 inhibited Toll-like receptor (TLR) 2, 4, 5, and 9 signaling, but not TLR3-dependent signaling, in macrophages. Ligand-mediated receptor trafficking to lipid rafts represents an early event in signal initiation of immune cells. Trafficking of TLR4 to lipid rafts in response to LPS was reactive oxygen species (ROS) dependent because it was inhibited by diphenylene iodonium, an inhibitor of NADPH oxidase, and in gp91(phox)-deficient macrophages. CO selectively inhibited ligand-induced recruitment of TLR4 to lipid rafts, which was also associated with the inhibition of ligand-induced ROS production in macrophages. TLR3 did not translocate to lipid rafts by polyinosine-polycytidylic acid (poly(I:C)). CO had no effect on poly(I:C)-induced ROS production and TLR3 signaling. The inhibitory effect of CO on TLR-induced cytokine production was abolished in gp91(phox)-deficient macrophages, also indicating a role for NADPH oxidase. CO attenuated LPS-induced NADPH oxidase activity in vitro, potentially by binding to gp91(phox). Thus, CO negatively controlled TLR signaling pathways by inhibiting translocation of TLR to lipid rafts through suppression of NADPH oxidase–dependent ROS generation.